MiR‐30c protects diabetic nephropathy by suppressing epithelial‐to‐mesenchymal transition in db/db mice - Zhao, Yanru (Aging Cell, 2017)
Epithelial‐to‐mesenchymal transition (EMT) plays a significant role in tubulointerstitial fibrosis, which is a hallmark of diabetic nephropathy. Thus, identifying the mechanisms of EMT activation could be meaningful. In this study, loss of miR‐30c accompanied with increased EMT was observed in renal tubules of db/db mice and cultured HK2 cells exposed to high glucose. To further explore the roles of miR‐30c in EMT and tubulointerstitial fibrosis, recombinant adeno‐associated viral vector was applied to manipulate the expression of miR‐30c. In vivo study showed that overexpression of miR‐30c suppressed EMT, attenuated renal tubulointerstitial fibrosis and reduced proteinuria, serum creatinine, and BUN levels. In addition, Snail1 was identified as a direct target of miR‐30c by Ago2 co‐immunoprecipitation, luciferase reporter, and Western blot assays. Downregulating Snail1 by siRNA reduced high glucose‐induced EMT in HK2 cells, and miR‐30c mimicked the effects. Moreover, miR‐30c inhibited Snail1‐TGF‐β1 axis in tubular epithelial cells undergoing EMT and thereby impeded the release of TGF‐β1; oppositely, knockdown of miR‐30c enhanced the secretion of TGF‐β1 from epitheliums and significantly promoted proliferation of fibroblasts and fibrogenesis of myofibroblasts, aggravated tubulointerstitial fibrosis, and dysfunction of diabetic nephropathy. These results suggest a protective role of miR‐30c against diabetic nephropathy by suppressing EMT via inhibiting Snail1‐TGF‐β1 pathway.